1981
DOI: 10.1002/hep.1840010306
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral treatment of chronic hepatitis B virus infection: Improvement in liver disease with interferon and adenine arabinoside

Abstract: Twelve of 32 patients lost HBeAg and DNA polymerase from their serum after completing antiviral therapy with interferon and/or adenine arabinoside. Three lost serum HBsAg as well. Loss of corresponding viral markers from hepatic tissue was also seen. There was improvement in symptoms, hepatic tests, and histologic findings in the 12 patients whose viral markers disappeared when compared to the 20 whose viral markers persisted despite treatment. These findings provide support for the use of antiviral agents in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

1982
1982
1999
1999

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…[20][21][22][23][24][25][26][27][28][29] In addition, histological assessments of patients in other studies of lamivudine have shown that liver biopsy features improve significantly during lamivudine-induced suppression of HBV replication. 5,30,31 Further controlled trials of prolonged lamivudine treatment are in progress to define the efficacy and safety of lamivudine therapy and maintenance of virological responses after drug withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27][28][29] In addition, histological assessments of patients in other studies of lamivudine have shown that liver biopsy features improve significantly during lamivudine-induced suppression of HBV replication. 5,30,31 Further controlled trials of prolonged lamivudine treatment are in progress to define the efficacy and safety of lamivudine therapy and maintenance of virological responses after drug withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…IFN treatment reduces hepatitis B virus-specific DNA-polymerase activity and other viral markers in the serum of patients with chronic hepatitis (22). Several viral markers also disappear or decrease in hepatic tissue (21). Other workers, however, observed no effect of IFN treatment except for a transient decrease in DNA-polymerase activity (26).…”
mentioning
confidence: 99%
“…Ara-A has been used in recent years in the treatment of chronic hepatitis B. It reduces, in a dose-dependent fashion, the serum levels of virus DNA-polymerase [34-381, with a loss of infectivity [39] and an overall improvement of liver disease [40] in some patients. However, ara-A also produces sideeffects, mostly gastrointestinal and neurological disturbances [41,42]; at doses higher than 25 mg.kg-'.day-', it also causes severe depression of bone marrow functions [43].…”
Section: Asialofetuin Conjugatesmentioning
confidence: 99%